Penerapan Peraturan Pemerintah Nomor 59 Tahun 2015 Terhadap Pembentukan Produk Hukum Daerah Pemerintah Provinsi Kepulauan Riau - Irwandi Irwandi (Universitas Internasional Batam, 2019)
The study aims to describe and analyze and identify the reasons behind the Riau Islands Provincial Government not yet applying Government Regulation No. 59 of 2015 to the establishment of regional legal products. This research was conducted using a sociological juridical approach. Lack of knowledge or information on regional equipment in the Riau Islands Provincial Government regarding the need for the participation of legislators in the formation of regional legal products, there is still a sectoral ego from the Riau Islands Province government as a representative of the central government in the regions, no sanctions if not including regulatory designers legislation in the formation of regional legal products.